Isolated Protein S Deficiency - Cause of Recurrent Stent Thrombosis - A Case Report - Choudhury, AK; Khalequzzaman, M; Hasem, S; Akhtaruzzaman, M; Jannat, S (Cardiovascular Journal, 2014)
Stent thrombosis (ST) is one of the major complications that occur in percutaneous coronary interventions (PCIs) with stents. Various factors have been attributed to the development of ST, and several strategies have been recommended for its management. Protein C or protein S deficiencies may uncommonly be responsible for coronary arterial thrombosis. We report a young woman with recurrent stent thrombosis due to the deficiency of protein S. After coronary stenting, stent thrombosis occurred two times despite aggressive medical therapy. This report suggests that the deficiency of protein C or S should be born in mind in a young patient with recurrent thrombotic events, and that anticoagulants in addition to antiplatelet agents considered in the presence of their deficiency DOI: http://dx.doi.org/10.3329/cardio.v6i2.18364 Cardiovasc. j. 2014; 6(2): 175-179